Distribution and management of non-native squirrels in Japan - Tamura, Noriko; Yasuda, Masatoshi (Frontiers in Ecology and Evolution, 2023)
Three species of alien squirrels have been confirmed to have been introduced in Japan: Tamias sibiricus, Callosciurus erythraeus (including the species complex C. finlaysonii), and Sciurus vulgaris. Japan is home to endemic squirrel species S. lis, Petaurista leucogenys, and Pteromys momonga, as well as endemic subspecies S. vulgaris orientis, T. sibiricus lineatus, and Pteromys volans orii. It is important to address the issue of damage to ecosystems caused by alien species, including the conservation of endemic species. Chipmunks (T. sibiricus) have become established in at least 11 of 47 prefectures, but no measures have been taken because the damage is not yet apparent. Pallas’s squirrels (C. erythraeus) that were reared in petting zoos for tourism purposes escaped and have become established in at least 17 localities in 13 prefectures. Because of the high population densities and significant damage caused by this species, removal measures have been implemented in at least 12 locations. The species is now eradicated or near eradication in four locations. Eurasian red squirrels (S. vulgaris) have become established at two sites in central Honshu and Kyushu. Due to possible hybridization with the Japanese squirrel (S. lis), trapping began in 2014 with the aim of eradication. This review summarizes the measures taken in Japan to conserve endemic species and emphasizes the importance of the involvement of researchers in early action.